Officers And Committees Of The American Institute Of Mining And Metallurgical Engineers Inc. 1922 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1922)
For the year ending February, 1923 PRESIDENT ARTHUR S. DWIGHT, District 0 NEW YORK, N. Y. PAST PRESIDENTS HERBERT HOOVER, District 4 WASHINGTON, D. C. EDWIN LUDLOW, District 0 NEW YORK, N. Y. FIRST VICE-PRESIDENT J. V. W. REYNDERS NEW YORK, N. Y. TREASURER CHARLES F. RAND NEW YORK, N. Y. SECRETARY FREDERICK F. SHARPLESS,. . . . . NEW YORK, N. Y. ASSISTANT SECRETARY PERCY E. BARBOUR NEW YORK, N. Y.